2006
DOI: 10.1097/01.ccm.0000235743.38172.6e
|View full text |Cite|
|
Sign up to set email alerts
|

Findings of the First Consensus Conference on Medical Emergency Teams*

Abstract: Patients needing an RRS intervention are suddenly critically ill and have a mismatch of resources to needs. Hospitals should implement an RRS, which consists of four elements: an afferent, "crisis detection" and "response triggering" mechanism; an efferent, predetermined rapid response team; a governance/administrative structure to supply and organize resources; and a mechanism to evaluate crisis antecedents and promote hospital process improvement to prevent future events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
559
1
36

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 733 publications
(608 citation statements)
references
References 11 publications
4
559
1
36
Order By: Relevance
“…On the basis of RRS features in widely cited articles [22][23][24] and the recommendations of a recent consensus statement, 5 we defined an RRS as having the following characteristics: (1) its primary responsibility is to intervene whenever hospitalized patients become unstable before cardiopulmonary arrest occurs; (2) it must primarily provide care outside the ICU and emergency department; (3) specific clinical criteria must be in place that define instability and trigger a call to the team; and (4) it must be expected to respond within a specified time. We defined these criteria in order to distinguish studies of RRSs from studies of cardiac arrest ("code blue") teams or traditional consulting services.…”
Section: Literature Search and Inclusion And Exclusion Criteriamentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of RRS features in widely cited articles [22][23][24] and the recommendations of a recent consensus statement, 5 we defined an RRS as having the following characteristics: (1) its primary responsibility is to intervene whenever hospitalized patients become unstable before cardiopulmonary arrest occurs; (2) it must primarily provide care outside the ICU and emergency department; (3) specific clinical criteria must be in place that define instability and trigger a call to the team; and (4) it must be expected to respond within a specified time. We defined these criteria in order to distinguish studies of RRSs from studies of cardiac arrest ("code blue") teams or traditional consulting services.…”
Section: Literature Search and Inclusion And Exclusion Criteriamentioning
confidence: 99%
“…On the basis of recommendations for the assessment of methodology for nonrandomized study designs, 25,26 we identified and abstracted 4 important determinants of internal validity ( Table 1). The consensus statement 5 recommends monitoring the effectiveness of RRSs by measuring the rate of unscheduled ICU admissions (defined as an unplanned admission to the ICU from a general ward 27 ) and cardiac arrests of patients who were not listed as "do not resuscitate" (DNR). As the definition of unscheduled ICU admission allows room for subjectivity, we considered the blinding of assessment of this outcome to study group assignment to be important, especially for retrospective studies.…”
Section: Example Of Rapid Response System Calling Criteria For Adultmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Although numerous studies have examined the clinical impacts of pediatric [2][3][4][5][6][7][8][9][10] and adult 11,12 METs, no studies have evaluated their financial costs and benefits.…”
mentioning
confidence: 99%